Shape tailored Cu2ZnSnS4 nanosheet aggregates for high efficiency solar desalination. (October 2019) - Zhang, Jin; Yang, Yawei; Zhao, Jianqiu; Dai, Zhonghua; Liu, Weiguo; Chen, Chaobo; Gao, Song; Golosov, D.A.; Zavadski, S.M.; Melnikov, S.N.
Graphical abstract: Highlights: Shape tailored CZTS NSAs are prepared via a low cost one-pot solvothermal method. The CZTS NSAs-based filter membranes are applied in a solar desalination device. Solar evaporation rate of the device is ˜1.54 kg/m 2 h under one sun irradiation. After desalination, the organic dyes can be degraded nearly 100%. Abstract: In this paper, the shape tailored high-purity kesterite phase Cu2 ZnSnS4 (CZTS) nanosheet aggregates (NSAs) were prepared in a low cost one-pot solvothermal method, and further fabricated into a salt-blocking membrane for solar desalination. The designed CZTS NSAs membrane-based solar steam generation device featured high solar absorptivity, low thermal energy loss and long-term stability, achieving a remarkable water evaporation rate of 1.54 kg/m 2 h and solar steam conversion efficiency of 78.85%. It is noteworthy that the quality of artificial seawater desalinated by evaporation was better than that of distilled water, and organic dyes, in particular, could be degraded by nearly 100%. It indicates that the CZTS NSAs membrane is likely to be one of the greatest potential substitutes for seawater desalination as well as repurification of urban reclaimed water and chemical wastewater.